Climatic controls on diffuse groundwater recharge across Australia - O. V. Barron; R. S. Crosbie; W. R. Dawes; S. P. Charles; T. Pickett; M. J. Donn (Hydrology and Earth System Sciences, 2012)
Reviews of field studies of groundwater recharge have attempted to investigate how climate characteristics control recharge, but due to a lack of data have not been able to draw any strong conclusions beyond that rainfall is the major determinant. This study has used numerical modelling for a range of Köppen-Geiger climate types (tropical, arid and temperate) to investigate the effect of climate variables on recharge for different soil and vegetation types. For the majority of climate types, the correlation between the modelled recharge and total annual rainfall is weaker than the correlation between recharge and the annual rainfall parameters reflecting rainfall intensity. Under similar soil and vegetation conditions for the same annual rainfall, annual recharge in regions with winter-dominated rainfall is greater than in regions with summer-dominated rainfall. The importance of climate parameters other than rainfall in recharge estimation is highest in the tropical climate type. Mean annual values of solar radiation and vapour pressure deficit show a greater importance in recharge estimation than mean annual values of the daily mean temperature. Climate parameters have the lowest relative importance in recharge estimation in the arid climate type (with cold winters) and the temperate climate type. For 75% of all soil, vegetation and climate types investigated, recharge elasticity varies between 2 and 4 indicating a 20% to 40% change in recharge for a 10% change in annual rainfall. Understanding how climate controls recharge under the observed historical climate allows more informed choices of analogue sites if they are to be used for climate change impact assessments.